The Buffalo of the North: Caribou (Rangifer tarandus) and Human Developments - Bergerud, A.T.; Jakimchuk, R.D.; Carruthers, D.R. (ARCTIC, 1984)
The demography, movement, and behaviour patterns of eight caribou populations (Kaminuriak, Nelchina, Central Arctic, Fortymile, Porcupine, British Columbia, Newfoundland, and Snohetta) exposed to industrial activities or transportation corridors are reviewed. Behaviour patterns of caribou encountering transportation corridors are explainable in terms of adaptive responses to natural environmental features. There is no evidence that disturbance activities or habitat alteration have affected productivity. Transportation corridors have adversely affected caribou numbers by facilitating access by hunters. There are no examples where physical features of corridors or associated disturbances have affected numbers or productivity. Caribou apparently have a high degree of resilience to human disturbance, and seasonal movement patterns and extent of range occupancy appear to be a function of population size rather than of extrinsic disturbance. The carrying capacity of the habitat is based on the space caribou need to interact successfully with their natural predators. Caribou must not be prevented from crossing transportation corridors by the construction of physical barriers, by firing lines created by hunting activity along a corridor, or by intense harassment - a loss in usable space will ultimately result in reduced abundance.Key words: caribou (Rangifer tarandus), disturbance, wolves, predation, overharvest, access Mots clés: caribou (Rangifer tarandus), dérangement, loups, predation, surchasse, l'accès aux chasseurs